A novel device for a vertical rocking isolation system with uplift allowed for industrial equipment and structures. (1st July 2020) - Reyes, Sergio I.; Almazán, José L.
Highlights: Development of an isolation device using unvulcanized high damping rubber in compression and tension. Development of a novel numerical model that involves hyperelasticity and a modified Bouc-Wen model. Three-dimensional vertical-rocking isolation system. Seismic protection of industrial equipment. Abstract: In this paper, a novel device called the "ISO3D-2G" is proposed for a three-dimensional vertical rocking isolation (VRI) system. The VRI system works by isolating critical vibration sources, e.g., earthquake events and operational high-frequency vibrations. In this work, only its performance as a seismic isolation system is studied. The ISO3D-2G is made of a steel structure and an elastomeric rubber system, offering improved properties as compared to previous versions of the device. The device is manufactured at a full scale and is experimentally tested. To represent the vertical non-linear hysteretic behavior of the device, a numerical model called the hyperelastic Bouc-Wen (HBW) model is developed. The HBW model combines a hyperelastic component (represented in this work by a third-order Ogden model) and a hysteretic component (represented by a modified BW model). The simply supported horizontal behavior of the device is represented through a non-linear 2D frictional hysteretic model. The HBW model is calibrated to fit the experimental data obtained in the test, and guidelines are provided for understanding and manually calibrating the model. The dynamic performance of the system is analyzed using time-history analyses with four records (three non-impulsive records and one impulsive record). Equations are presented for the motion of the system. For the three non-impulsive seismic records, the observed behavior was similar to that in conventional lateral isolation systems. Horizontal force reduction ratios between 7.4 and 10.9 were obtained. The maximum shear base remained below 23% of the total weight of the structure, even considering the three components of the ground motion. In addition, vertical force reduction ratios between 2 and 3.8 were obtained, demonstrating that the vertical isolation effect was satisfactory. However, for an impulsive seismic record, there was a significant change in the patterns of behavior, owing to the significant uplift of two of the four devices. Despite this, the structure remained stable, and the lateral isolation effect was preserved. Finally, it was concluded that using vertically flexible devices with high damping in the base of structures to generate a rocking isolation mechanism is an effective approach to reducing the seismic demand, even though the isolated modes of the structure do not take periods longer than 2.0 s. Although there was no lateral translation at the base, the VRI system isolated the structure by allowing lateral and vertical displacement of the center of mass.